The Pyrrhic Victory of Game Studies: Assessing the Past, Present, and Future of Interdisciplinary Game Research. (September 2017) - Deterding, Sebastian
Although game studies are widely viewed as an interdisciplinary field, it is unclear how interdisciplinary they actually are. In response, this article reads scientometric data and game studies editorials, handbooks, and introductions through the lens of interdisciplinarity studies to assess game studies' status as an interdiscipline. It argues that game studies show drivers and hurdles typical for interdisciplines. Yet instead of establishing themselves as the broad umbrella interdiscipline of digital game research, they are becoming one narrow cultural studies multidiscipline within the growing and diversifying field of game research and education. Researchers from fields like human–computer interaction or communication are abandoning game studies venues in favor of disciplinary ones—ironically thanks to game studies legitimizing game research. This article suggests that a design orientation and cross-disciplinary boundary objects such as middle range theories could help to broaden, deepen, and secure future interdisciplinary game research.